A fundamental investigation on welding flux tunability geared towards high heat input submerged arc welding for shipbuilding applications - H Yuan; H Tian; Y Zhang; Z Wang; C Wang (The Australasian Institute of Mining and Metallurgy, 2024)
Submerged arc welding (SAW) is one of the significant metal-joining processes for manufacturing marine vessels, steel pipes, and offshore structures with high deposition rate and engineering reliability. Welding flux serves several essential functions, including atmospheric shielding, arc stabilisation, bead morphology control and weld metal (WM) refinement. Therefore, from a thermodynamic point of view, the focus for flux design and WM compositional/microstructural modification has been placed to elucidating the transfer pathways and mechanisms of major alloying elements, such as Si, Mn, Ti and O during welding. To this end, a thermodynamic model has been established to predict alloying element contents in the WM. Such functions are enabled by the physicochemical properties of the fluxes, which are inherently rooted in the nature of the fluxes. A unique yet systematical investigation, including physicochemical property changes and structural evolution behaviours, has been conducted over the wide range of fluxes applied to actual welding of EH36 shipbuilding steels. Combined with spectroscopic methods, structural behaviours of network formers such as SiO2, Al2O3 and TiO2 and network modifiers such as MgO, MnO and CaO have been illustrated. Viscosity and ionic conductivity have been found to be positively associated with the degree of polymerisation.